EXPANSION OF THE MEANING OF INCLUSION OF OFFENSES IN THE LATEST CRIMINAL CODE AND ITS INFLUENCE ON LAW ENFORCEMENT FOR TERRORISM CRIMES - Safri HM (Bhayangkara Law Review, 2024)
The renewal of the offense of inclusion in Article 20 of Law Number 1 of 2023 is certainly interesting to discuss further regarding how the renewal of the offense of inclusion will affect the enforcement of criminal law in Indonesia, especially in the field of law enforcement for criminal acts of terrorism, because of the expansion of the meaning of inclusion This will have its own influence on law enforcement. What is the meaning of the expansion of inclusion offenses in Law Number 1 of 2023? How does it affect law enforcement for criminal acts of terrorism? The research method used in this research is a normative juridical research method. The material studied uses primary, secondary and tertiary legal materials. The results of the research show that the expansion of included offenses in Law Number 1 of 2023 concerning the Criminal Code actually has an influence in the form of strengthening the implementation of law enforcement contained in Law Number 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism. The expansion of the offense of participation, especially to the material of encouraging other people to commit criminal acts by giving or promising something, abusing power or dignity, committing violence, using threats of violence, committing misdirection, or by providing opportunities, means or information, where there is a compatibility between the extensions of the offense of participation can certainly work in harmony in maximizing law enforcement efforts in the form of punishment for criminal offenses contained in legal regulations related to terrorism.